Clinical validation of visual LAMP and qLAMP assays for the rapid detection of Toxoplasma gondii - Cao, Zhi; Zhang, Ke; Yin, Dehua; Zhang, Qiaoya; Yu, Ying; Wen, Jianxin; Ni, Hongbo (Frontiers in Cellular and Infection Microbiology, 2022)
Humans are exposed to Toxoplasma gondii infection as pet cats gradually become family members and represent an increasing public health risk worldwide. Toxoplasmosis diagnosis constitutes an important measure for disease prevention and control. In this study, real-time fluorescence quantitative loop-mediated isothermal amplification (qLAMP) and visual LAMP detection technologies were established to conduct tests of Toxoplasma gondii based on the membrane DNA extraction method, and the optimal detection mix was determined by adding the protective reagent trehalose and screening the concentrations of Mg2+ and dNTPs. Paraffin and lyophilization were used to reduce and even remove aerosol pollution, constructing a detailed anti-contamination protocol. Based on the positive standard plasmid DNA, the LODs of qLAMP and visual LAMP were 92 copies/μL and 92 copies/μL, and the standard curve of qLAMP was Y=2.9503X+20.8992 with R2=0.99. The applicability of the qLAMP and visual LAMP assays in disease diagnosis was assessed by evaluating 200 clinical cat faeces samples. The assays showed good diagnostic consistency, with kappa values of 1.0 and 0.99 compared with TaqMan qPCR, respectively. Compared with TaqMan qPCR, the diagnostic specificity/sensitivity of qLAMP and visual LAMP were 100%/100% and 100%/80%, respectively. The qLAMP and visual LAMP assays reported here are rapid and simple tests without extensive sample preparation and have a short turnaround time within 60 min, making them suitable for point-of-care testing.